Effect of motion artifact on digital camera based heart rate measurement - Hassan, M.A. (Institute of Electrical and Electronics Engineers Inc., 2017)
Remote health monitoring is an emerging field in biomedical technology. Digital camera based heart rate measurement method is a recent development which would make remote health monitoring reliable and sustainable in future. This paper presents an investigation on the effect of motion artifact on digital camera-based heart rate measurement. The paper will discuss details on the principles and effects of motion artifacts on photoplethysmography signals. An experiment is conducted using publicly available MAHNOB-HCI database. We have investigated the effects of static scenarios, scenarios involving rigid motion and scenarios involving non-rigid motion. The experiment was tested on state of the art digital camera based heart rate measuring methods. The results showed the effectiveness of the methods and provide a direction to overcome/minimize the effect of motion artifacts for future research. © 2017 IEEE.